Cell-Free Hemoglobin Is Associated With Increased Vascular Resistance and Reduced Peripheral Perfusion in Severe Malaria. (6th November 2019) - Kingston, Hugh W F; Ghose, Aniruddha; Rungpradubvong, Voravut; Satitthummanid, Sudarat; Herdman, M Trent; Plewes, Katherine; Ishioka, Haruhiko; Leopold, Stije J; Sinha, Ipsita; Intharabut, Benjamas; Piera, Kim; McNeil, Yvette; et al.
Abstract: Background: In severe falciparum malaria, unlike sepsis, hypotension on admission is uncommon. We hypothesized that low nitric oxide bioavailability due to the presence of cell-free hemoglobin (CFH) increases vascular tone in severe malaria. Methods: Patients with severe malaria (n = 119), uncomplicated malaria (n = 91), or suspected bacterial sepsis (n = 56), as well as healthy participants (n = 50), were recruited. The systemic vascular resistance index (SVRI) was estimated from the echocardiographic cardiac index and the mean arterial pressure. Results: SVRI and hematocrit levels were lower and plasma CFH and asymmetric dimethylarginine levels were higher in patients with malaria, compared with healthy participants. In multivariate linear regression models for mean arterial pressure or SVRI in patients with severe malaria, hematocrit and CFH but not asymmetric dimethylarginine were significant predictors. The SVRI was lower in patients with suspected bacterial sepsis than in those with severe malaria, after adjustment for hematocrit and age. Plasma CFH levels correlated positively with the core-peripheral temperature gradient and plasma lactate levels and inversely with the perfusion index. Impaired peripheral perfusion, as reflected by a low perfusion index or a high core-peripheral temperature gradient, predicted mortality in patients with severe malaria. Conclusions: CFH is associated with mean arterial pressure, SVRI, and peripheral perfusion in patients with severe malaria. This may be mediated through the nitric oxide scavenging potency of CFH, increasing basal vascular tone and impairing tissue perfusion. Abstract : Hypotension is a common feature of bacterial sepsis but infrequent in severe malaria. the level of cell-free hemoglobin, which scavenges the vasodilator nitric oxide, was increased during severe malaria and associated with higher blood pressure and vascular resistance but impaired peripheral perfusion.